2021
DOI: 10.1136/bmjopen-2020-045306
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in self-reported financial conflicts of interest disclosures by physicians: a systematic review

Abstract: BackgroundThere is a high prevalence of financial conflicts of interest (COI) between physicians and industry.ObjectivesTo conduct a systematic review with meta-analysis examining the completeness of self-reported financial COI disclosures by physicians, and identify factors associated with non-disclosure.Data sourcesMEDLINE, Embase and PsycINFO were searched for eligible studies up to April 2020 and supplemented with material identified in the references and citing articles.Data extraction and synthesisData w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…The Internal Committee of Medical Journal Editors (ICMJE) and many clinical practice guideline-developing organizations including the American Gastroenterological Association (AGA) and the American Society of Clinical Oncology (ASCO) have expanded the FCOI declaration policy to a longer lookback period such as three years before publication [12,20]. As our study showed, the shorter lookback period underestimated the magnitude of FCOIs among guideline authors, though the shorter ADA COI declaration period might have led to a more accurate COI declaration than other clinical guidelines previously documented [13,17,29,31,34,38,[44][45][46]. However, longer look-back periods, such as three years prior to guideline publication, were established based on the many previous cases of potential harm to patients caused by FCOIs and the increased public demand for greater transparency [1,4,5].…”
Section: Discussionmentioning
confidence: 61%
“…The Internal Committee of Medical Journal Editors (ICMJE) and many clinical practice guideline-developing organizations including the American Gastroenterological Association (AGA) and the American Society of Clinical Oncology (ASCO) have expanded the FCOI declaration policy to a longer lookback period such as three years before publication [12,20]. As our study showed, the shorter lookback period underestimated the magnitude of FCOIs among guideline authors, though the shorter ADA COI declaration period might have led to a more accurate COI declaration than other clinical guidelines previously documented [13,17,29,31,34,38,[44][45][46]. However, longer look-back periods, such as three years prior to guideline publication, were established based on the many previous cases of potential harm to patients caused by FCOIs and the increased public demand for greater transparency [1,4,5].…”
Section: Discussionmentioning
confidence: 61%
“…Similarly to US and Danish studies, COI disclosures of Australian authors are often incomplete. 3 These discrepancies highlight the need for more transparent and comprehensive COI reporting. Our study adds to the evidence that underreporting of COI is likely widespread globally.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicts of interest (COI) were defined by the Institute of Medicine’s Committee on Conflict of Interest in Medical Research, Education, and Practice as a set of “circumstances that create a risk that professional judgments or actions regarding a primary interest will be unduly influenced by a secondary interest.” 1 Prior quantitative bioethics research has characterized COI among physician authors of biomedical 2 and pharmacology textbooks, 3 psychiatry’s Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition), 4 and clinical practice guidelines. 5 , 6 However, there is limited research on the potential COI among authors and editors of online clinical resources, such as UpToDate and DynaMed. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…1 Prior quantitative bioethics research has characterized COI among physician authors of biomedical 2 and pharmacology textbooks, 3 psychiatry's Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition), 4 and clinical practice guidelines. 5,6 However, there is limited research on the potential COI among authors and editors of online clinical resources, such as UpToDate and DynaMed. [7][8][9] UpToDate and DynaMed are online, subscription-based products used by physicians to assist in clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation